BESIII production with distributed computing. Issue 3 (December 2015) - Zhang, X M; Yan, T; Zhao, X H; Ma, Z T; Yan, X F; Lin, T; Deng, Z Y; Li, W D; Belov, S; Pelevanyuk, I; Zhemchugov, A; Cai, H
Abstract: Distributed computing is necessary nowadays for high energy physics experiments to organize heterogeneous computing resources all over the world to process enormous amounts of data. The BESIII experiment in China, has established its own distributed computing system, based on DIRAC, as a supplement to local clusters, collecting cluster, grid, desktop and cloud resources from collaborating member institutes around the world. The system consists of workload management and data management to deal with the BESIII Monte Carlo production workflow in a distributed environment. A dataset-based data transfer system has been developed to support data movements among sites. File and metadata management tools and a job submission frontend have been developed to provide a virtual layer for BESIII physicists to use distributed resources. Moreover, the paper shows the experience to cope with lack of grid experience and low manpower among the BESIII community.